2016
DOI: 10.1093/mnras/stw3023
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the dark matter content of NGC 1291 using hydrodynamic gas response simulations

Abstract: We present a pilot study on the nearby massive barred galaxy NGC 1291, in which we use dynamical modelling to constrain the disc mass-to-light ratio (M/L), thus breaking the degeneracy between the baryonic and dark matter in its central regions. We use the gas, specifically the morphology of the dust lanes on the leading side of the bar, as a tracer of the underlying gravitational potential. We run a large number of hydrodynamic gas response simulations, in potentials obtained directly from near-infrared image… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 74 publications
(125 reference statements)
1
24
0
Order By: Relevance
“…10 and Table 2) is significantly less severe (depending on aperture), yet these models still prefer dark matter density slopes that are NFW rather than contracted. Our DMFs fall among the estimates for generally disc-like galaxies at z = 0 from the two DiskMass and SWELLS samples analysed by Courteau & Dutton (2015) and the Kranz et al (2003); Fragkoudi et al (2017) data -see Fig. 13.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…10 and Table 2) is significantly less severe (depending on aperture), yet these models still prefer dark matter density slopes that are NFW rather than contracted. Our DMFs fall among the estimates for generally disc-like galaxies at z = 0 from the two DiskMass and SWELLS samples analysed by Courteau & Dutton (2015) and the Kranz et al (2003); Fragkoudi et al (2017) data -see Fig. 13.…”
Section: Discussionsupporting
confidence: 67%
“…13, by plotting the DFMs within the simulated 3D stellar half mass radii 8 . We also show the Genzel et al (2017) data, the Courteau & Dutton (2015) DMF derivations for z = 0 galaxies, a modified version of the Courteau & Dutton (2015) SWELLS derivations that uses the Chabrier IMF, and a set of disc observations by Kranz et al (2003) and Fragkoudi et al (2017) that assume different systematics. The data are separated into two panels: the left-hand panel explores some of the systematic uncertainties in the z = 0 observations, and the right-hand panel shows the difference between z = 0 and z = 2.…”
Section: Disc-dominated Galaxies Across Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…We first obtain a stellar mass map for the galaxy from the 3.6µm NIR image, which is cleaned from foreground stars and is deprojected to be face-on (Querejeta et al 2015). To obtain the stellar mass surface density we assign a massto-light ratio of M/L = 0.6 (Meidt et al 2014;Röck et al 2016;Erroz-Ferrer et al 2016;Fragkoudi et al 2017) to each pixel in the NIR image, which has been shown to be suitable for a wide range of ages and metallicities of the underlying stellar populations (Meidt et al 2014). We then assign a height function in order to account for the thickness of the disc (assuming a relation between the scaleheight and scalelength of the galaxy according to Kregel et al 2002), and integrate over the density distribution to obtain the gravitational potential of the disc.…”
Section: Gravitational Potentialmentioning
confidence: 99%
“…This function, which has the form f tape (r) = exp((r − r 1 ) 2 )/(2d 2 ) smoothly truncates the gaseous disc for r > r 1 , in order to avoid density discontinuities or numerical issues at the boundary of the simulation box. 6 For more details on this process see Section 4 ofFragkoudi et al 2017 …”
mentioning
confidence: 99%